Effect of Antigonon leptopus extract in corn starch-glycerol based film as colourimetric indicator film for monitoring fish freshness - Ho, P.X.J.; Mohd Zin, Z.; Portman, K.L.; Hasmadi Mamat; Rusli, N.D.; Scott, D.J. (Rynnye Lyan Resources, 2024)
A colourimetric indicator can be used to test the freshness of fish in a rapid, straightforward and non-destructive manner. Anthocyanin, a natural dye found in Antigonon leptopus flowers, has a sensitive colour reactivity to a wide range of pH levels and can be made into colourimetric indicator films on a laboratory scale, making it a viable replacement for artificial dyes. The study's purpose was to see how the concentration of A. leptopus extract affected the colourimetric assessment of fish freshness. Ethanol was used to extract anthocyanin from A. leptopus. FTIR and pHrespond spectroscopies were used to characterise the extracts. Colourimetric indicator films were developed to assess fish freshness by incorporating A. leptopus extract into a corn starch-glycerol matrix via the solution casting method, with concentrations of 10%, 30% and 50%, respectively. The effect of A. leptopus extract on visual aspects, thickness, morphology, FTIR spectra, UV-Vis spectra and colour responses was analysed. Microbial analysis, TVB-N contents, firmness, and pH of the fish samples were analysed after storage. The colour of the original films became darker as the extracted content increased. There was no significant (p>0.05) effect of A. leptopus extract on film thickness. SEM micrographs revealed that the composite films had homogeneous and whitish granules on the surface and that increasing the A. leptopus extract concentration caused the films to become rougher. FTIR and UV-Vis spectroscopies showed successful binding between A. leptopus extracts and corn starch-glycerol film. With increasing pH, the colour change of the films exposed to pH = 3-11 solutions was no significant difference due to improper storage. An increase in the microbial population, TVB-N content and pH was observed over the storage period as a result of fish deterioration. Colour changes were also identified in the film which became darker. Overall, colourimetric indicator film with 50% A. leptopus extract was found to be the optimal formulation since it had the highest values in ∆E* during progressive spoilage of fish.